ANATOMIC PATTERNS OF RIGHT RENAL VEIN - Shaheen, Robina; Jamil, Muhammad Nasir; Farooq, Umar (Journal of Ayub Medical College Abbottabad, 2018)
Background: Preoperative surgical planning assumes a central role in avoiding catastrophic outcomes of a surgery in the field of renal transplantation, and other urological procedures. This study was aimed to study the different anatomic patterns of human renal venous system. Methods: It is a descriptive cross-sectional study including 50 adult male cadavers with well-preserved kidneys, renal vasculature and the inferior vena cava. Cadavers with deformed or congenitally anomalous kidney, evidence of surgery, solitary kidney, tumours of kidneys or injured renal vessels / inferior vena cava were excluded from the study. The kidneys, renal veins and the inferior vena cava were exposed. After securing inferior vena cava fifty ml mixture of Indian ink and gelatine was injected into renal veins via inferior vena cava and was allowed to solidify. Following this, the renal venous anatomy was studied. Results: Twenty-eight cadavers had their right renal vein formed by 2 tributaries (56%), 13 (26%) had 3 tributaries, 5 (10%) had 4 tributaries, 1 cadaver had a posterior tributary (2%), while 3 cadavers had other numbers of tributaries (6%). Out of total 50 cadavers 40 (80%) had normal distribution of right renal vein. Additional renal veins were found in 14 (7%) cadavers, double renal veins in 1 (2%) and proximally double renal veins in 2 cadavers (4%). Conclusions: There is considerable variation in renal venous anatomy. Knowledge of common venous patterns is necessary for minimizing intra-operative damage to renal anatomy and to prevent intra- and post-operative complications. Keywords: renal vein; anatomy; kidney